Occupational stress and work fatigue among vessel crews - Dwi Kurniawan; Hendra Djamalus (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Fatigue contributes to approximately 20% of occupational incidents and is identified as an underlying factor in 25% of fatal and serious accidents. This condition is often exacerbated by high job demands, which can induce emotional strain in the form of occupational stress. Globally, occupational stress affects an estimated 264 million workers. Purpose: To analyze the relationship between occupational stress and work fatigue among small-vessel crew members at PT X. Method: This quantitative study used a cross-sectional design involving 54 small-vessel crew members. Data were collected using the Multidimensional Fatigue Inventory (MFI-20) and Depression Anxiety Stress Scale (DASS-21) questionnaires. The data were analyzed using the chi-square test. Results: A significant relationship was found between occupational stress and work fatigue among small-vessel crew members, with a significance value of 0.013 (p < 0.05) and an odds ratio (OR) of 5.714. Among small-vessel crew members experiencing occupational stress, 23 individuals (95.8%) also experienced work fatigue. Conclusion: The findings indicate that occupational stress is significantly associated with work fatigue and represents an important risk factor for fatigue development among small-vessel crew members. Small-vessel crew members experiencing occupational stress had 5.714 times higher odds of experiencing occupational fatigue compared with those without occupational stress.